“Y aun así, volando”: an epic of resilience - Lojo, María Rosa (Anales de Literatura Hispanoamericana, 2021)
Reflection on the first Argentinean generation of children of Spanish exiles, on the language and the maternal saying as a key to identity, on an "I" from where?